In-the-loop or on-the-loop? Interactional arrangements to support team coordination with a planning agent - Fischer, Joel E.; Greenhalgh, Chris; Jiang, Wenchao; Ramchurn, Sarvapali D.; Wu, Feng; Rodden, Tom (Wiley, 2017)
In this paper we present the study of interactional arrangements that support the collaboration of headquarters (HQ), field responders and a computational planning agent in a time-critical task setting created by a mixed-reality game. Interactional arrangements define the extent to which control is distributed between the collaborative parties.We provide two field trials, one to study an “on-the-loop” arrangement in which HQ monitors and intervenes in agent instructions to field players on demand, and the other to study a version that places headquarters more tightly “in-the-loop”. The studies provide and understanding of the sociotechnical collaboration between players and the agent in these interactional arrangements, by conducting interaction analysis of video recordings and game log data. The first field trial focuses on the collaboration of field responders with the planning agent. Findings highlight how players negotiate the agent guidance within the social interaction of the collocated teams. The second field trial focuses on the collaboration between the automated planning agent and the headquarters. We find that the human coordinator and the agent can successfully work together in most cases, with human coordinators inspecting and ‘correcting’ the agent-proposed plans. Through this field trial-driven development process, we generalise interaction design implications of automated planning agents around the themes of supporting common ground and mixed-initiative planning.